2022
DOI: 10.1002/pbc.29644
|View full text |Cite
|
Sign up to set email alerts
|

Clinical group and modified TNM stage for rhabdomyosarcoma: A review from the Children's Oncology Group

Abstract: The Children's Oncology Group (COG) uses Clinical Group (CG) and modified Tumor Node Metastasis (TNM) stage to classify rhabdomyosarcoma (RMS). CG is based on surgicopathologic findings and is determined after the completion of initial surgical procedure(s) but prior to chemotherapy and/or radiation therapy. The modified TNM stage is based on clinical and radiographic findings and is assigned prior to any treatment. These systems have evolved over several decades. We review the history, evolution, and rational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 90 publications
0
21
0
Order By: Relevance
“…However, patients aged <13 years, who accounted for 64.8% of the overall cohort, were unevenly distributed, which may potentially lead to bias. As for the tumor sites, according to the historical Children's Oncology Group risk stratification, bladder, or prostate sites are considered unfavorable, presenting a relatively low survival rate, therefore, cannot be treated as low risk ( 19 21 ). Our multivariate analysis of survival showed that the survival rate of bladder or prostate tumors was 1.86 times lower compared to other favorable sites, which is in accordance with other studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, patients aged <13 years, who accounted for 64.8% of the overall cohort, were unevenly distributed, which may potentially lead to bias. As for the tumor sites, according to the historical Children's Oncology Group risk stratification, bladder, or prostate sites are considered unfavorable, presenting a relatively low survival rate, therefore, cannot be treated as low risk ( 19 21 ). Our multivariate analysis of survival showed that the survival rate of bladder or prostate tumors was 1.86 times lower compared to other favorable sites, which is in accordance with other studies.…”
Section: Discussionmentioning
confidence: 99%
“…The orbit is designated a favorable primary site by the Intergroup Rhabdomyosarcoma Study Group (IRSG) modified tumor, node, metastasis (TNM) staging system. [1][2][3] The standard treatment approach to ORMS on IRSG and subsequent Children's Oncology Group (COG) studies has been biopsy followed by chemotherapy and radiotherapy, so that, at presentation, most patients have group III disease. 4 The highest failure-free survival (FFS) rate reported for patients with group III ORMS occurred on Intergroup Rhabdomyosarcoma Study IV (IRS-IV) (3-year FFS, 94%; overall survival [OS], 98%); however, intensive therapy was administered with 26.4 g/m 2 cyclophosphamide or 126 g/m 2 ifosfamide and 50.4-59.4 Gray (Gy) of radiation, increasing the risks of long-term morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, despite aggressive combination therapy, no further significant improvements have been made for the treatment of children with high-risk disease or recurrent disease (5-year survival <30% and 17%, respectively) [ 2 ]. Favorable prognostic factors include a primary tumor site in the orbit and tumors that are located in the non-parameningeal head and neck region and genitourinary sites, with the exception of the bladder and prostate; from patients aged 1–9 years; a lack of distant metastases at diagnosis; a clinical stage based on the classification of the primary procedure; a maximum tumor diameter ≤5 cm; and embryonal histology [ 1 , 7 ]. According to a report from the COG (The Children’s Oncology Group), PAX-FOXO1 fusion results in unfavorable outcomes in children with RMS [ 8 ].…”
Section: Introductionmentioning
confidence: 99%